Diagnosis and tactics of surgical treatment of early postoperative intrapleural complications - Nazyrov, Feruz G.; Khudaibergenov, Shuhrat N.; Irisov, Orticaly Tulaevich (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Surgical procedures on the lungs and trachea are at risk of the occurrence of complications representing a significant impact on postoperative mortality. This paper describes problems related to definition of complications in chest surgery, time-frames of their occurrence and possible causes concerning surgical and anesthesiologic approach. It focuses on several issues including bleeding, empyema, lung tissue leak and chylothorax. The possibility of using minimally invasive techniques in diagnostic and therapeutic treatment is also discussed.